(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2010)
This prospective ongoing study conducted in University Cardiac Center, BSMMU, Dhaka from July 2004 to April 2006. 100 patients (mean age 52.4±6.2 years) underwent Percutaneous Transluminal Coronary angioplasty and stenting (PTCA & stenting) were evaluated. This study was designed to evaluate the short term angiographic and clinical results of stentangioplasty during hospital stay. The study group of 100 patients consisted of 88 (88%) men and 12 (12%) women. About risk factors 36 (36%) had hypertension, 30 (30%) were smoker, 20 (20%) suffered from diabetes mellitus, 14 (14%) had family history of ischaemic heart disease. Average Left ventricular ejection fraction was 54.2±7. Target vessel PTCA were done on 130 vessels, intracoronary stent implanted in 124 vessels, direct stenting was done in 80 cases, failed PTCA were in 4 (4%) cases, and three patients had dissection. The native vessels had a mean reference diameter of 2.89 mm and their luminal diameter increased significantly after percutaneous coronary intervention (PCI). Thombolysis in myocardial infarction (TIMI) flow analysis showed most of the patients had TIMI-1 flow (95,73%) before the procedure and maximum patients achieved TIMI-3 flow (91, 70%) after the procedure with significant clinical improvement. All the patients were discharged by one to three days of the procedure with improvement of their clinical condition. So PTCA and Stenting is a safe and effective technique with high procedural success rate and good short-term (hospital) clinical results in the native coronary artery lesions. Key words: Coronary artery diseases; PTCA and stenting. DOI: 10.3329/jbcps.v26i1.4230 J Bangladesh Coll Phys Surg 2008; 26: 26-31